Revolução passiva e o papel formativo da filosofia no Ensino Médio - Paolo Nosella; Alessandra Maria Martins Gaidargi (EccoS – Revista Científica)
This paper is a work in progress, in which we present preliminary notes that will be further developed in essays. We argue that the theoretical fruitfulness of the category "passive revolution" that Antonio Gramsci developed in his writings, provides thorough analysis and critique of the media revolution underway. The first part will illustrate the concept of "passive revolution" Gramsci. The second part will focus on the passive revolution in brazilian culture in general, and currently on the indiscriminate and extensive use of media by young high school students. The third part is a defense of the philosophy education proposed in middle school as an "instrument" of unit and responsible reconstruction of the world’s concept for young teens.